A Gestão de resíduos sólidos em contextos intraorganizacionais: um estudo a partir da UFPA - ALMEIDA, Lúcia de Fátima (Universidade Federal do Pará, 2012)
This dissertation focuses on answering the following question: How did the process of implementing the Selective Collection Solidarity Program at the Federal University of Para. The program was established by Decree No. 5940 of 25th October 2006 and aims at the destination of recyclable material produced in the federal government agencies of the administration direct and indirect to associations and cooperatives of collectors. This action, despite restrictions on their disposal, contributes to poverty alleviation and environmental impact in natural areas. The objective of this research is to understand and analyze the process of implementing the Joint Selective Collection Program at UFPA. It is based on the Neo-institutionalism of Hall and Taylor and comparisons of theoretical approaches of Olson and Ostrom on the Behavioral Theory of Collective Action in the production of a Public Good. The methodology used was descriptive and qualitative. The theory led to fieldwork for the observation techniques, semi-structured interviews and documentary research. 25 interviews were conducted with staff members of the University Council of UFPA, directors and coordinators of Academic Units as well as general service staff members. As a result, was found the need of a interaction work within their own Academic Units, these together and, at the same time with the Senior Management. In Ostrom, was found the support to the theoretical direction because your conception of common use and collective decision of cooperation based on reciprocity and trust between people. She adds elements to the Olson‟s Behavioral Theory of Collective Action and show that works in search of the common good are possible if exist rules that everyone are subjected to the benefits of arising externalities. With institutional approaches of the collective action presented, this study intends to contribute with the application of Environmental Management in Public Administration. The achieved results can lead to the practice of Selective Collection Solidarity of UFPA encouraging managers in the interior of state to engage in program.